LIGNAN, CINNAMIC AMID VÀ FLAVONON GLYCOSIT TỪ GỖ CÂY DÓ TÀU (AQUILARIA SINENSIS) - Phương Dung, Phạm Thị; Thanh Hương, Nguyễn Thị; Thuỷ, Trịnh Thị; Sung, Trần Văn (Vietnam Journal of Chemistry, 2012)
Agarwood is one of the famous incense, valuable products in tropical forest and is used as a sedative, analgesic and digestive in traditional medicines. From the wood of Aquilaria sinensis growing wild in Son La province, syringaresinol (1), (E)-N-feruloyltyramin (2), (E)-N-[2-hydroxy-2-(4-hydroxyphenyl)ethyl]ferulamid (3), (Z)-N-[2-hydroxy-2-(4-hydroxyphenyl)ethyl]ferulamid (4), 5,4’-dimethoxyflavone-7-O-β-D-xylopyranosyl-(1->6)-β-D-glucopyranoside (5), were isolated. Their structures were elucidated on the basis of MS and NMR spectral data. Keywords: Chinese eaglewood; Aquilaria sinensis; syringaresinol; feruloyltyramine; cinnamic amide.